Effect of Ethanolic Caesalpinia sappan Fraction on In Vitro Antiviral Activity against Porcine Reproductive and Respiratory Syndrome Virus - Arjin, Chaiwat; Hongsibsong, Surat; Pringproa, Kidsadagon; Seel-audom, Mintra; Ruksiriwanich, Warintorn; Sutan, Kunrunya; Sommano, Sarana Rose; Sringarm, Korawan (Veterinary sciences, 2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a major epidemic in pig production, leading to economic losses in the pig industry worldwide. The use of medicinal plants with antiviral properties might be useful help to prevent and control PRRSV outbreaks. Caesalpinia sappan (CS) heartwood is an important herbal ingredient used in Thai folk medicine, possessing various biological activities, including antiviral activity. The present study focuses on the in vitro antiviral activity against PRRSV of a semi-purified fraction of ethanolic CS crude extract using preparative high-performance liquid chromatography. Qualification of the fractions illustrating positive antiviral activity was carried out with liquid chromatography–quadrupole time-of-flight mass spectrometry. The preparative chromatography separated the crude extract into six consecutive fractions, among which the first fraction showed potential antiviral activity by inhibiting PRRSV replication in a MARC-145 monolayer (virus titer 2.75 median tissue culture infective dose (TCID50)/mL (log10) vs. 9.50 median log10 TCID50/mL of the control) at 72 h post-infection, and this fraction included byakangelicin, brazilin, naringenin, and brazilein. These results provide useful information for further study to effectively develop the CS bioactive antiviral compounds against PRRSV as a feed additive or veterinary drug in the pig industry.